1996
DOI: 10.1002/(sici)1520-6300(1996)8:4<427::aid-ajhb2>3.0.co;2-v
|View full text |Cite
|
Sign up to set email alerts
|

Fat areas on the extremities in normal weight and overweight children and adolescents: Comparison between age-related and weight-related changes in adiposity

Abstract: The purpose of the study was to compare changes in fat distribution in association with obesity and puberty in adolescent boys and girls. Fat areas at the ulnar, triceps, thigh, and calf regions were measured in normal weight prepubertal children (P) and adolescents (N), and overweight adolescents (O). There were significant differences in fat areas at the four sites between N and O of both sexes, especially in the proximal extremities (triceps, thigh) in boys. On the other hand, fat areas on the extremities o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Regarding the differences between groups, hip girth was significantly higher in the NWF than in the NWM but not in the overweight/obese group. These results are similar to those found in previous research, in which females had a greater accumulation of peripheral fat in the limbs or hips [ 90 , 91 ]. However, in obese individuals, the hypothalamic-pituitary-adrenal axis may be overly sensitive, breaking the balance between the lipogenic and lipolytic effects of the hormones related to fat accumulation, cortisol, and insulin may be the reason why no differences were found between OWM and OWF [ 5 , 90 ].…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the differences between groups, hip girth was significantly higher in the NWF than in the NWM but not in the overweight/obese group. These results are similar to those found in previous research, in which females had a greater accumulation of peripheral fat in the limbs or hips [ 90 , 91 ]. However, in obese individuals, the hypothalamic-pituitary-adrenal axis may be overly sensitive, breaking the balance between the lipogenic and lipolytic effects of the hormones related to fat accumulation, cortisol, and insulin may be the reason why no differences were found between OWM and OWF [ 5 , 90 ].…”
Section: Discussionsupporting
confidence: 92%
“…This difference is likely to be due to the difference in body composition, that is, the percent body fat, between male and female adolescents. Females, especially during adolescence, show a higher body fat mass than males(18, 19). Nakanishi et al (19) reported that the increased body fat mass and enhanced insulin resistance in pubertal females were associated with higher leptin levels in these subjects.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, a simple measurement of the external circumference cannot precisely represent this kind of inner fibrotic replacement. Furthermore, adiposity can be affected by anatomical location and sex 58 ; the larger is the area of the involved subcutaneous fat compartment in an individual patient, the greater can be the discrepancy between the inner change and external limb circumference. Taking the above findings into consideration, a lower correlation of the four indices with the SCDR might be expected.…”
Section: Discussionmentioning
confidence: 99%